Patients with unstable control have a poorer dietary intake of vitamin K compared to patients with stable control of anticoagulation - Sconce, Elizabeth; Khan, Tayyaba; Mason, Jennifer; Noble, Faye; Wynne, Hilary; Kamali, Farhad (Thrombosis and Haemostasis, 2005)
Evidence suggests that alterations in the dietary intake of vitamin K can affect anticoagulation response to warfarin. It is possible that a low and erratic intake of dietary vitamin K is at least partly responsible for the variable response to warfarin in patients with unstable control of anticoagulation. Twenty-six patients with unstable and twenty-six with stable control of anticoagulation completed dietary records of all foods and drinks consumed on a daily basis for two consecutive weeks. The mean daily intake of vitamin K in unstable patients was considerably lower than that for stable patients during the study period (29±17μg v. 76±40µg). The logarithm of vitamin K intake was consistently and significantly lower in the unstable patients than the stable patients over the two week period (5.9±0.4µg v. 6.9±0.5µg; p<0.001; 95% CI: 0.7–1.2). Changes in vitamin K intake between weeks 1 and 2 of the study were negatively correlated with changes in International Normalised Ratio (INR) amongst the unstable patients, however this failed to reach significance (r=-0.25; p=0.22). Daily supplementation with oral vitamin K in unstable patients could lead to a more stable anticoagulation response to warfarin.
Keywords: Warfarin; anticoagulation; diet; vitamin K